2016
DOI: 10.1111/acel.12525
|View full text |Cite
|
Sign up to set email alerts
|

mTOR regulates the expression of DNA damage response enzymes in long‐lived Snell dwarf, GHRKO, and PAPPA‐KO mice

Abstract: SummaryStudies of the mTOR pathway have prompted speculation that diminished mTOR complex‐1 (mTORC1) function may be involved in controlling the aging process. Our previous studies have shown diminished mTORC1 activity in tissues of three long‐lived mutant mice: Snell dwarf mice, growth hormone receptor gene disrupted mice (GHRKO), and in this article, mice deficient in the pregnancy‐associated protein‐A (PAPPA‐KO). The ways in which lower mTOR signals slow aging and age‐related diseases are, however, not well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 54 publications
(88 reference statements)
3
52
1
2
Order By: Relevance
“…Based on our results and other research data we can postulate that a post transcriptional modification may be achieved by NDRG1 interaction with the HSP90 protein (53). The mTOR signaling pathway may also be involved, since the downstream regulator CCR4-NOT may upregulate NDRG1 (54,55). Such post transcriptional regulation may act along with post translational modification, such as e.g.…”
Section: Discussionsupporting
confidence: 63%
“…Based on our results and other research data we can postulate that a post transcriptional modification may be achieved by NDRG1 interaction with the HSP90 protein (53). The mTOR signaling pathway may also be involved, since the downstream regulator CCR4-NOT may upregulate NDRG1 (54,55). Such post transcriptional regulation may act along with post translational modification, such as e.g.…”
Section: Discussionsupporting
confidence: 63%
“…Modulation of mTOR activity suppresses proteins that are involved in chromosomal integrity and enhances DNA damage–induced apoptosis in cancer cells (31, 32), whereas the deletion of mTOR causes a defective DDR in mitotic cells (33). More recently, DDR factors were demonstrated to be up‐regulated via post‐transcriptional mechanism in 3 genetic mouse models with the mTORC1 pathway attenuated (34).…”
mentioning
confidence: 99%
“…Furthermore, mTORC1-dependent phosphorylation of the transcription factor TFEB promotes association of TFEB with members of the 14-3-3 family of proteins, thereby forcing its retention in the cytosol (88). However, the network connecting the mTOR pathway to the DNA damage response continues to be elucidated (92)(93)(94)(95). A recent study (95) showed that mTOR/S6K signaling leads to phosphorylation and subsequent degradation of RNF168, and hyperactivation of mTOR via LKB1 leads to decreased levels of RNF168 and increases DNA damage.…”
Section: Discussionmentioning
confidence: 99%